Ácaros asociados a dos especies de Odontotaenius (Coleoptera: Passalidae) en México - Barrios-Torres, Pilar Liliana (Universidad de Costa Rica, 2015)
Mites can establish association with different arthropods as coleopterans families Scarabaeidae and Passalidae. Passalids are distributed in tropical and templates zones, and until now, more than 200 species of mites have been associated to them. One of the relationships between passalids and mites is the phoresy where one small animal (the phoretic) seeks out and attaches to another animal (the host) for transportation. Herein, we studied the mites associated to O. zodiacus and O. striatopunctatus; for this, 80 Odontotaenius with mites were reviewed; passalids were collected in and under decaying logs from six states of Mexico, and were individually kept in vials with 80% ethanol. The specimens were carried to the laboratory and mites removed with fine-pointed forceps under stereo microscope. The mites were stored with 80 % alcohol until some were cleared with lacto-phenol and mounted in Hoyer’s solution. We found 1 945 mites belonging to 13 families (Acaridae, Ascidae, Diarthrophallidae, Digamasellidae, Diplogyniidae, Euzerconidae, Heterocheylidae, Histiostomatidae, Klinckowstroemiidae, Laelapidae, Megisthanidae, Trematuridae, and Uropodidae) and 42 species, being the most abundant species Anoetus sp. For O. striatopunctatus (16 specimens) we found 562 mites (95 ♀♀, 34 ♂♂, 197 hypopus, 234 deutonymph, 2 tritonymph) of 11 families and 22 species; the most abundant were Uropodidae (42 %) and Histiostomatidae (26 %). While for O. zodiacus (64 specimens) were found 1 383 mites (300 ♀♀, 204 ♂♂, 608 hypopus, 139 deutonymphs, 133 tritonymphs) of 10 families and 30 species; the most abundant were: Diartrophallidae, Acaridae, and Histiostomatidae (23 % for the two first and 21 % for third). The high abundance and richness was in O. zodiacus, likewise Margalef (S´) and Shanon-Winner (H´) indexes were higher in this species (O. zodiacus S´ = 4.05, H´ = 2.2; O striatopunctatus S´ = 3.34, H´ = 1.94), while Equity (EH) was similar to both hosts (O. zodiacus EH = 0.64; O. striatopunctatus EH = 0.63). The mites were found principally in the protected zone of the passalid’s body, as under elytron, membranous wings, and in the clefts of the ventral region of the passalid, and, in minor proportion, on the head and coxal regions. From our findings, 12 species were new records for the Mexican passalids: Abrotarsala cuneiformis, A. obesa, A. pyriformis, Brachytremella sp., Diarthrophallus cartwrighti, D. crinatus, Lombardiniella sp., Trichodiplogynium carlosi, T. sahlbergi, T. hirsutum and Trichodiplogynium sp., and additional studies may help describe and understand these mites-passalids associations.